Sweet country [videorecording (DVD)] - Thornton, Warwick; Brown, Bryan, 1947-; Morris, Hamilton; Wright, Thomas M., 1983- (Sony Pictures Home Entertainment, 2018)
Sam, a middle-aged Aboriginal man, works for a preacher in the outback of Australia's Northern Territory. When Harry, a bitter war veteran, moves into a neighboring outpost, the preacher sends Sam and his family to help Harry renovate his cattle yards. But Sam's relationship with the cruel and ill-tempered Harry quickly deteriorates, culminating in a violent shootout in which Sam kills Harry in self-defense.